Gender and Perception: Implementation of Web-based Character Assessment in Science Learning - Darmaji, Darmaji; Astalini, Astalini; Kurniawan, Dwi Agus; Aldila, Febri Tia; Pathoni, Haerul (LPPM Undiksha, 2022)
The use of information technology in education is a real impact of the development of science and technology. The development of technology in the field of education has led to innovations in assessment systems such as web-based assessments. The use of web-based assessment to assess student character will bring up different student perceptions which can be influenced by gender differences. Therefore, this study was designed to analyze how the comparison of students' perceptions of the application of web-based character assessment in science learning based on gender differences. This research is quantitative research with a survey approach which was conducted by filling out a student perception questionnaire containing 30 statements. The sample in this study was 120 students who were selected by purposive sampling. The data obtained will be analyzed using descriptive statistics and inferential statistics with hypothesis testing in the form of one-way Anova test to determine whether there is a comparison of student perceptions of the application of web-based character assessment in science learning based on gender differences. The results showed that male students' perceptions showed more positive results than female students' perceptions of the application of web-based character assessment in science learning.